Paper Patching Versus Watchful Waiting of Traumatic Tympanic Membrane Perforations: A Meta‐Analysis. (21st April 2021) - Simani, Liam; Oron, Yahav; Handzel, Ophir; Eta, Rani Abu; Warshavsky, Anton; Horowitz, Gilad; Muhanna, Nidal; Ungar, Omer J.
Abstract : Objectives/Hypothesis: The aim of the study was to investigate the healing rates, the restoration of hearing, and the time for complete healing of paper patching versus watchful waiting for traumatic tympanic membrane perforations (TTMPs). Study Design: Systematic review with meta analysis. Methods: Publications were selected by a search on "PubMed, " "Embase, " and "Web of Science." A meta‐analysis of risk ratios for paper patching (intervention arm) and watchful waiting (control arm) was performed. Results: Five studies describing 393 TTMPs were included in the quantitative meta‐analysis. TTMP healing rates ranged between 84.2% and 95.2% in the intervention arm and between 76.7% and 84.8% in the control arm. The pooled risk ratio of healed TTMPs was significantly higher in the intervention arm than in the control arm (risk ratio: 1.12, 95% confidence interval: 1.04–1.21). Conclusions: TTMPs have high healing potential with and without intervention. The healing rate of paper patching was superior to that of watchful waiting alone. Level of Evidence: NA Laryngoscope, 131:2091–2097, 2021